One case of kissing hypermelanic nevus. - Zhang, R.; Zhu, W. (European Journal of Pediatric Dermatology, 2010)
A 10-year-old girl was referred to the dermatology clinic for the evaluation of an asymptomatic pigmented lesion on her right eye involving since birth both the upper and lower lids, which appeared united when the eyelids were closed. Because of analogy to kissing melanocytic nevus, the lesion was described as "kissing hypermelanic nevus". This case is highly illustrative of the embryologic timing of the genetic event locally, which leads to café-au-lait type hyperpigmentation.